Dispersionless BKP Hierarchy and Quadrant Löwner Equation - Takebe, T. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
We show that N-variable reduction of the dispersionless BKP hierarchy is described by a Löwner type equation for the quadrant.